Bridge management 5 inspection, maintenance, assessment and repair : proceedings of the 5th International Conference on Bridge Management, organised by the University of Surrey, 11-13 April 2005 - Parke, G. A. R.; Disney, P. (Thomas Telford, 2005)
Focusing on bridge management, this fifth volume contains over eighty papers which span the fields of bridge management systems, inspection methods, structural assessment and maintenance strategies. It also includes reliability and risk management techniques. It is aimed at bridge owners and engineers engaged in bridge design, assessment, repair.